Psychological counseling process: application of rational emotive behaviour therapy to treat 'Panic Attack' case - Yasmin Othman Mydin; Fatimah Yusooff (Elsevier, 2024)
Procedia - Social and Behavioral Sciences Volume 5, 2010, Pages 416-420